2017
DOI: 10.3390/ijms18020327
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Gramineae and Fabaceae Soda Lignins

Abstract: Some agricultural residues such as wheat or barley straw, as well as certain fast-growing plants like Leucaena leucocephala and Chamaecytisus proliferus, could be used as raw materials for the paper industry as an alternative to traditional plants (eucalyptus, pine, etc.). In the present study, four types of lignin obtained from the spent liquors produced by the pulping processes using the abovementioned feedstocks were isolated and characterized. Lignin samples were acquired through an acid precipitation from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 44 publications
5
40
0
Order By: Relevance
“…The band at 629 cm −1 was attributed to C–S stretching, in spite of the fact that no S was detected by EA (detection limit < 0.01 wt %) of the same materials. Such C–S stretching bands have been reported in the literature, as a consequence of acidic precipitation of lignins with sulfuric acid 22.…”
Section: Resultssupporting
confidence: 64%
“…The band at 629 cm −1 was attributed to C–S stretching, in spite of the fact that no S was detected by EA (detection limit < 0.01 wt %) of the same materials. Such C–S stretching bands have been reported in the literature, as a consequence of acidic precipitation of lignins with sulfuric acid 22.…”
Section: Resultssupporting
confidence: 64%
“…So, a detailed knowledge of lignin structure, composition and purity is required in order to determine its behaviour in different potential applications. In this sense, characterization of residual lignins from Kraft and soda-anthraquinone pulping of agriculture residues such as olive tree pruning [97] and wheat or barley straw [98], as well as vegetables like L. leucocephala, C. proliferus, and H. funifera [99,100], has been carried out.…”
Section: Lignin Applicationsmentioning
confidence: 99%
“…There are many useful species and numerous amounts of them have been cultivated since ancient times, mainly due to their food and medicinal potential, although there are several other utilities. Libidibia ferrea (L. ferrea) , popularly known as jucá or pau-ferro, is a species of the Leguminosae family with multiple medicinal uses [1]. Studies performed with species of the Leguminosae family have demonstrated antihelmintic, antimalaria, anti-inflammatory, and analgesic activity [25].…”
Section: Introductionmentioning
confidence: 99%